Prevalence of respiratory symptoms among children in rural Myanmar-disease burden assessment attributable to household biomass smoke. Issue 5 (August 2016) - Rumchev, Krassi; Win, Thet; Bertolatti, Dean; Dhaliwal, Satvinder
More than three billion people continue to rely on solid fuels as their primary source of domestic energy which is associated with elevated concentrations of indoor air pollutants and increased morbidity and mortality both in adults and children. In Myanmar, solid fuel including coal and biomass (such as dung, crop and charcoal) is the main source of energy used in households. A community-based pilot study was conducted in rural Myanmar with the aim to determine the prevalence of childhood respiratory symptoms in association with the use of biomass for cooking. A total of eighty households were recruited and monitored for exposure to particulate matter with size less than 2.5 μm in aerodynamic diameter (PM2.5 ) and carbon monoxide (CO). In addition, mothers were interviewed to understand their cooking habits, some house characteristics and children's respiratory health. The study found that PM2.5 and CO were significant contributors for the prevalence of acute respiratory infections and trouble breathing among young children. House characteristics including mosquito coil, associated with children's respiratory health. The study confirms that domestic environments in developing countries, like Myanmar, continue to have significant health impacts on children.